Positive relationship of hypertensive retinopathy with carotid intima--media thickness in hypertensive patients. Issue 10 (October 2020) - Zhang, Wenbo; Li, Jun; Zhao, Liang; Zhang, Jing; She, Haicheng; Meng, Ying; Peng, Yuan; Shang, Kun; Zhang, Yadi; Gu, Xiaopeng; Chen, Xuling; Zhang, Yan; et al.
Abstract : Objectives: We aimed to explore the relationship of hypertensive retinopathy with carotid intima--media thickness (CIMT), and to examine the possible effect modifiers in Chinese adults with hypertension. Methods: We conducted a cross-sectional study of 12 342 hypertensive patients with complete exit site visit data from the China Stroke Primary Prevention Trial. CIMT was measured by carotid ultrasonography. Hypertensive retinopathy was diagnosed according to the Keith--Wagener--Barker classification. Results: The mean (SD) CIMT among study participants was 739.9 (111.4) μm. Compared with patients with grade 1 hypertensive retinopathy or without hypertensive retinopathy, a significantly higher CIMT level (β, 7.63, 95% CI: 2.54--12.73) was observed in patients with grade 2–4 hypertensive retinopathy. Moreover, the association between hypertensive retinopathy (grade 2–4 versus grade 1 or normal) and CIMT was stronger in participants of younger age (<60 years; β, 13.70, 95% CI: 5.65--21.75; versus ≥60 years; β, 1.03, 95% CI: −5.58 to 7.63; P interaction = 0.006); or with lower total homocysteine levels [<12.1 μmol/l (median); β, 12.70, 95% CI: 5.98--19.42; versus ≥12.1 μmol/l; β, 2.07, 95% CI: −5.63 to 9.78; P interaction = 0.030). None of the other variables, including sex, BMI, study centers, treatment group, SBP, triglycerides, total cholesterol, fasting blood glucose, folate, serum creatinine, current smoking and alcohol drinking, significantly modified the relation of hypertensive retinopathy with CIMT levels. Conclusion: Hypertensive retinopathy (grade 2 and higher) was significantly associated with increased CIMT in hypertensive patients. The association was stronger in those of younger age or with lower total homocysteine levels. Abstract : Supplemental Digital Content is available in the text